Potential for Tofu Industry Liquid Waste Pollution in Mejing Village, Candimulyo Subdistrict, Magelang - Riva Ismawati; Rina Rahayu (Indonesian Journal of Science and Education, 2024)
This research is intended to analyze the quality of tofu liquid waste, analyze the quality of river water around the tofu industry in Mejing Village and analyze government policies in managing tofu liquid waste. The research method used is grab sampling, observation, and interviews to obtain primary data. Secondary data from journal articles and research reports are used to support primary data. The research results show that the quality of tofu liquid waste has a pH of 2.8-33, a temperature of 41-51 oC and is not in accordance with established quality standards. Tofu liquid waste also has a pungent sour odor, yellowish color, and contains many suspended particles. Disposal of tofu liquid waste into the waters causes the river flowing in Mejing Village to be dirty and indicates light to heavy pollution. The government has set quality standards for wastewater produced by the tofu industry. Unfortunately, the tofu industry in Mejing Village does not comply with this regulation properly. The low awareness of tofu industry players to manage liquid waste is caused by various factors. Good communication between the government and industry players is needed so that industry players know how to process the liquid waste they produce. The government needs to supervise the application of government regulations related to the management of tofu liquid waste and provide sanctions to industries that violate it. Planning for a communal IPAL as well as an appropriate solution must be realized immediately so that the problem of tofu liquid waste in the tofu industry center in Mejing Village can be resolved immediately.